Knowledge on and preventive practices of cholera in Al-Mahweet - Yemen, 2018: a cross-sectional study - Fekri Dureab; Yasameen Al-Qadasi; Hani Nasr; Marwah Al-Zumair; Taha Al-Mahbashi (IWA Publishing, 2021)
Yemen has experienced one of the world's worst cholera outbreaks in the recent history of cholera records. This study aims to identify knowledge and practices among people of Al-Mahweet governorate toward cholera infection, which can play a critical role in reducing cholera morbidity and shaping the public health response. A cross-sectional study was conducted in an area of high cholera prevalence in 2018 using structured questionnaires. Most community respondents were able to correctly identify the symptoms and risk factors of cholera. While 65% of the respondents in this study knew that proper disposal of human waste is an essential measure of cholera prevention, only 11% of the respondents knew that proper washing of fruits and vegetables lowers the risk of cholera infection. About 62.5% of households did not treat water for safe drinking. Water was scarce in about 30% of households and near-home defecation was observed in about 23%. In conclusion, this study reveals several gaps in different aspects of hygienic and preventive practices including water treatment, waste disposal, and defecation practices. Cholera response should contain comprehensive health promotion interventions to improve the public's knowledge and enhance healthy practices. Stakeholders should support communities with sustainable water and sanitation systems. HIGHLIGHTS Cholera outbreak in fragile situation.; Raising community awareness for behavioural changes.; Water and sanitation measures in households.;